Electronic word of mouth against product purchasing decisions of vindex snack Tanjung Palas (with elaboration likelihood model approach) - Rina Sri Wahyuni; N Nopianti; Adi Aspian Nur (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2023)
MSMEs must be technologically literate in utilizing marketing patterns, one of which is Electronic Word of Mouth with the Elaboration Likelihood Model approach, which can increase people's purchasing decisions by improving the image or brand of MSME products in Indonesia. This study aims to evaluate the effect of Electronic Word of Mouth in the decision process to purchase Vindex Snack products using the Elaboration Likelihood Model approach. The results of this study indicate that the influence of Electronic Word Of Mouth has a negative contribution to the product purchasing decision process. While the power of Electronic Word Of Mouth by using two routes, namely the Central Route and the Peripheral Route, with an information quantity indicator of 80%, means that the quantity of information is needed in making product purchasing decisions. The indicator for buying Vindex Snack products shows excellent results, with a presentation of 75%.